Konstruksi Kemiskinan dalam Perspektif Suku Madura - Romadhan, Sukron; Masduqi, Mahfud (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to understand the perception of Madurese people towards cultural and structural poverty in Plakpak Pegantenan Village, Pamekasan. Cultural poverty refers to cultural factors that influence poverty, such as values, norms, and habits that hinder economic progress. Meanwhile, structural poverty is caused by systemic factors, such as government policies, access to education, and employment opportunities. Through qualitative methods with empirical research types, this study collected data from in-depth interviews and participant observations. The results of the study indicate that Madurese people in Plakpak Pegantenan Village have a complex understanding of poverty, which includes both cultural and structural aspects. These findings are expected to provide insight for policy makers in designing poverty alleviation programs that are more effective and in accordance with the local context. the existence of cultural poverty, can be seen from the symptoms and social conditions that are visible in poor culture, namely apathy towards the development of science, an attitude of resignation to fate, wasteful in shopping and consumptive and there is dependence on the environment, quick to give up (despair) when facing problems, there is a feeling of uselessness, a feeling of temperament or like to be emotional when facing problems, geographically located in remote areas or far from metropolitan cities and the emergence of thoughts of helplessness in starting a more decent life process.